2017
DOI: 10.5617/njhe.3581
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and children’s need for hospital services. Implications for need-based resource allocation models

Abstract: Abstract:We investigate whether parents´ socioeconomic status affects children´s need for hospital services, and potential implications for need-based resource allocation models. Data are from somatic hospital stays by children below the age of 11 in Norway in 2011. Socioeconomic status is measured by parents' educational level or income. We find that the educational gradient is dominating the income gradient, and the effects are strong: Hospital expenditures of a child whose mother (father) has not completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Larger numbers represented higher educational level; 0 indicated less than primary education and 8 indicated a doctorate or equivalent, while 9 was not classified and regarded as missing. Educational level was recoded into three categories: low (0-2), medium (3)(4)(5) and high (6)(7)(8). The number of siblings was computed each year according to birth year, and analysed as a dichotomous variable; only child or child with siblings.…”
Section: Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Larger numbers represented higher educational level; 0 indicated less than primary education and 8 indicated a doctorate or equivalent, while 9 was not classified and regarded as missing. Educational level was recoded into three categories: low (0-2), medium (3)(4)(5) and high (6)(7)(8). The number of siblings was computed each year according to birth year, and analysed as a dichotomous variable; only child or child with siblings.…”
Section: Definitionsmentioning
confidence: 99%
“…Kaarbøe and Carlsen found that for hospital admissions in children under the age of 11 in Norway, the educational gradient dominated the income gradient for SES. 7 Halldòrsson et al found that education was a more important determinant of healthcare utilisation for children than the financial situation of the families in Nordic countries. 16 Unanswered questions and future research Our data did not allow firm conclusions about a causal relationship, neither between medical needs nor nonmedical factors, and differences in hospital admission rates among children of parents with different educational level.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation